Polybenzimidazole / porous SiO2 microsphere hybrid high-temperature membrane, preparation method and application
Through the hybrid high-temperature membrane of polybenzimidazole and graded porous SiO2 microspheres, combined with phosphoric acid solution immersion and ultrasonic dispersion technology, the mechanical properties and thermal stability of the high-temperature proton exchange membrane are solved, and high proton conductivity and excellent Thermal stability, suitable for high-temperature proton exchange membrane fuel cells.
Patent Information
- Application Number
- CN202411223072.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-13
AI Technical Summary
When the existing high-temperature proton exchange membrane is above 100°C, although the use of high-boiling acid as the proton carrier improves the proton conductivity, it reduces the mechanical properties and thermal stability, making it difficult to achieve high proton conductivity, mechanical properties and thermal stability at the same time. sex.
The hybrid high-temperature film of polybenzimidazole and graded porous SiO2 microspheres is used to form a dispersion during the drying process and soak it in a phosphoric acid solution. Combined with ultrasonic dispersion and vacuum drying technology, a high-temperature film with excellent mechanical properties and thermal stability is prepared. Hybrid film.
It realizes the maintenance of high proton conductivity and mechanical strength under high temperature conditions, while improving the thermal stability of the membrane and meeting the performance requirements of high-temperature proton exchange membrane fuel cells.
Smart Images

Figure CN119119727A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of high-temperature proton exchange membranes, and relates to a polybenzimidazole / porous SiO2 microsphere hybrid high-temperature membrane, a preparation method and an application thereof. Background Art
[0002] As a non-renewable resource, petroleum resources will cause environmental pollution, climate change and other problems during use, which will pose a serious threat to human development. Therefore, it is urgent to find some new energy sources that can replace petroleum resources. Among them, hydrogen energy has the characteristics of abundant sources, high energy density and high calorific value, and is a very good energy storage carrier. At present, hydrogen fuel cells are the most common terminal application of hydrogen energy. As early as the 1960s, hydrogen fuel cells have been used in aerospace. After entering the 1970s, with the advancement of technology and the continuous reduction of costs, hydrogen fuel cells have gradually been used in various fields, including power generation, automobiles, ships and drones. Hydrogen fuel cells are power generation devices that directly convert the chemical energy of hydrogen and oxygen into electrical energy. Compared with internal combustion engines, hydrogen fuel cells have high energy conversion efficiency and no emission of any harmful pollutants. Among them, the most common type of hydrogen fuel cell on the market is proton exchange membrane fuel cell. According to the different operating temperatures, proton exchange membrane fuel cells are divided into low-temperature proton exchange membrane fuel cells (LT-PEMFC) and high-temperature proton exchange membrane fuel cells (HT-PEMFC). The operating temperature of LT-PEMFC is below 100°C, while the operating temperature of HT-PEMFC is between 100 and 200°C. The high temperature and low humidity operating conditions give HT-PEMFC many significant advantages: (1) improving the tolerance of platinum catalyst to CO; (2) accelerating electrode reaction kinetics; (3) simplifying water management and thermal management systems; (4) increasing gas diffusion rate; (5) reducing technical costs, etc. In summary, the development of HT-PEMFC has become one of the key research directions for the development of hydrogen fuel cells.
[0003] As the core component of the battery, the research of high-temperature proton exchange membranes must become a top priority. Since water molecules will turn into water vapor above 100°C, high-temperature proton exchange membranes usually use high-boiling acid (phosphoric acid, sulfonic acid) instead of water molecules as proton carriers. Although it can improve the proton conductivity of the exchange membrane, it reduces the mechanical properties and thermal stability of the exchange membrane. How to obtain a high-temperature proton exchange membrane with both high proton conductivity and high mechanical properties and thermal stability is a technical problem that needs to be solved urgently. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a polybenzimidazole / porous SiO2 microsphere hybrid high temperature membrane, wherein the hybrid high temperature membrane is mainly composed of a soluble aromatic ether type polybenzimidazole (hereinafter referred to as aromatic ether type polybenzimidazole), a sulfonic acid group and an imidazole group modified hierarchical porous SiO2 microsphere (hereinafter referred to as porous SiO2 microsphere); the structure and chemical formula of the porous SiO2 microsphere are as shown in the attached figure. Figure 6 shown.
[0005] Furthermore, the preparation method of the polybenzimidazole / porous SiO2 microsphere hybrid high temperature membrane comprises the following steps:
[0006] The porous SiO2 microspheres and the aromatic ether type polybenzimidazole are dispersed in a solvent in a mass ratio of 1:99 to 1:4 to form dispersion 1 and dispersion 2, respectively. The concentrations of the porous SiO2 microspheres and the aromatic ether type polybenzimidazole in the solvent are both 40 to 50 g / L. The dispersion 1 and the dispersion 2 are mixed into a casting solution, ultrasonically dispersed evenly, poured onto a clean glass plate, dried at 80 to 120°C for 30 to 50 h, and then vacuum dried at 100 to 120°C for 10 to 2 After 10 hours, a hybrid membrane is obtained, and then the hybrid membrane is immersed in a phosphoric acid solution with a mass fraction of 70-90%, and immersed at 80-130°C for 24-48 hours, and then the excess phosphoric acid on the surface of the hybrid membrane is wiped off with filter paper, and then dried at 100-120°C for 3-5 hours to obtain a polybenzimidazole / porous SiO2 microsphere hybrid high-temperature membrane; the solvent is one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone or dimethyl sulfoxide.
[0007] Furthermore, the preparation method of the porous SiO2 microspheres comprises the following steps:
[0008] (1) Hexadecyltrimethylammonium bromide (CTAB) and urea are mixed in a mass ratio of 4:3 to 5:2, and deionized water is added and stirred until dissolved, wherein the total mass concentration of the CATB and urea in the deionized water is 30 to 50 g / L, and then cyclohexane, isopropanol and tetraethyl orthosilicate (TEOS) solution are added under stirring, wherein the volume ratios of cyclohexane, isopropanol and tetraethyl orthosilicate (TEOS) to deionized water are 60 to 90 vol. %: 1, 2 to 5 vol. % respectively. :1 and 5-10vol.%:1, continue stirring at 30-50°C for 20-60min, continue stirring at 70-90°C for 12-24h, then cool down, add anhydrous ethanol solution of the same volume as deionized water, centrifuge at 8000-10000r / min for 5-10min, wash with ethanol and deionized water for 3-5 times, dry under vacuum at 60-80°C for 20-30h, and calcine at 500-600°C for 4-8h to obtain hierarchical porous SiO2 microspheres;
[0009] (2) dissolving the hierarchical porous SiO2 microspheres obtained in step (1) in toluene, wherein the concentration of the hierarchical porous SiO2 microspheres is 10-20 g / L, adding triethylamine, wherein the volume ratio of triethylamine to toluene is 1:400-1:300, stirring and ultrasonicating for 30-60 min, and then adding (3-mercaptopropyl)trimethoxysilane (MPTS) under magnetic stirring, wherein the molar ratio of MPTS to the hierarchical porous SiO2 microspheres is 1:5-3:5, reacting at room temperature for 5-12 h, centrifuging, washing with ethanol 3-5 times, drying at 60-80° C. for 4-10 h, and then dispersing in 30%-40% hydrogen peroxide, stirring at room temperature for 3-8 h, washing with ethanol and deionized water 3-5 times respectively, and drying at 60-80° C. for 6-12 h to obtain sulfonated hierarchical porous SiO2 microspheres;
[0010] (3) Degassing the sulfonated graded porous SiO2 microspheres obtained in step (2) at 90-120° C. in a vacuum, and then adding imidazole, wherein the mass ratio of the sulfonated graded porous SiO2 microspheres to imidazole is 1:20-1:10; and then evaporating and adsorbing at 90-120° C. in a vacuum for 5-30 hours to obtain porous SiO2 microspheres.
[0011] Furthermore, the preparation method of the aromatic ether polybenzimidazole comprises the following steps:
[0012] 3,3'-diaminobenzidine (DAB) and 4,4'-diphenyl ether dicarboxylic acid (OBA) were mixed in a molar ratio of 1:1 to 6:5, and then PPMA solvent was added, wherein the concentrations of DAB and OBA in the PPMA solvent were both 1 to 2 mol / L. Under mechanical stirring and nitrogen protection, the mixture was reacted at 140 to 190°C for 8 to 10 hours, and then poured into deionized water to obtain a black long strip polymer. The polymer was crushed and washed with deionized water. 3 to 6 times, added to a 5 to 15 wt% sodium bicarbonate solution, washed at 40 to 60° C. for 36 to 60 hours, washed with deionized water until the solution is neutral, filtered, and vacuum dried at 80 to 120° C. for 20 to 30 hours to obtain an aromatic ether type polybenzimidazole; the PPMA solvent is a mixture of phosphorus pentoxide and methane sulfonic acid, and the mass ratio of the phosphorus pentoxide to the methane sulfonic acid is 1:10 to 1:8; the synthesis route of the aromatic ether type polybenzimidazole is as follows:
[0013]
[0014] Wherein n is a positive integer, n=100~160.
[0015] The present invention also provides the application of the polybenzimidazole / porous SiO2 microsphere hybrid high-temperature membrane in the field of high-temperature proton exchange membrane fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is a curve comparison diagram of the change of phosphoric acid adsorption capacity of the polybenzimidazole / porous SiO2 microsphere hybrid high-temperature membrane obtained in Examples 4-8 over time;
[0017] Figure 2 is a curve comparison of the proton conductivity of the polybenzimidazole / porous SiO2 microsphere hybrid high-temperature membrane obtained in Examples 4-8 as a function of temperature;
[0018] Figure 3 is a plane scanning electron microscope image of the polybenzimidazole / porous SiO2 microsphere hybrid high temperature membrane obtained in Example 7;
[0019] Figure 4 is a cross-sectional scanning electron microscope image of the polybenzimidazole / porous SiO2 microsphere hybrid high temperature membrane obtained in Example 7, and the inset is an enlarged cross-sectional scanning electron microscope image;
[0020] Figure 5 is a tensile curve diagram of the polybenzimidazole / porous SiO2 microsphere hybrid high temperature membrane obtained in Example 7;
[0021] Figure 6 1 is the structural diagram and chemical formula of the porous SiO2 microspheres obtained in Example 2. DETAILED DESCRIPTION
[0022] Example 1
[0023] Preparation of sulfonated hierarchical porous SiO2 microspheres (s-GMSi):
[0024] Take 6.0g of hexadecyltrimethylammonium bromide (CTAB) and 3.0g of urea, mix them, add 200ml of deionized water and stir until dissolved. Then add 150mL of cyclohexane and 5mL of isopropanol under stirring, and add 15mL of tetraethyl orthosilicate (TEOS). Continue stirring at 40℃ for 30min, then continue stirring at 80℃ for 16h, cool down, add 200ml of anhydrous ethanol, centrifuge at 10000r / min for 5min, wash with ethanol and deionized water 4 times, and dry at 70℃ under vacuum for 24h. Then calcine at 550℃ for 5h to obtain hierarchical porous SiO2 microspheres (GMSi microspheres);
[0025] 0.3 g of GMSi microspheres were dispersed in 25 mL of toluene, and 50 μL of triethylamine was added, followed by stirring and ultrasonication for 40 min. Under magnetic stirring, 340 μL of (3-mercaptopropyl) trimethoxysilane (MPTS) was added, reacted at room temperature for 24 h, centrifuged, washed with ethanol 4 times, and dried at 60 ° C for 8 h to obtain SiO2 spherical particles 1, and then the SiO2 spherical particles 1 were dispersed in 3 mL of 30% hydrogen peroxide, stirred at room temperature for 6 h, and then washed with ethanol and deionized water for 3 times, respectively, and dried at 70 ° C for 10 h to obtain sulfonated hierarchical porous SiO2 microspheres (s-GMSi).
[0026] Example 2
[0027] Preparation of porous SiO2 microspheres (IM@s-GMSi):
[0028] 1 g of the sulfonated graded porous SiO2 microspheres (s-GMSi) obtained in Example 1 was degassed at 100°C in vacuum for 12 h, and then 15 g of imidazole and the degassed s-GMSi microspheres were evaporated and adsorbed at 120°C in vacuum for 30 h to obtain porous SiO2 microspheres (IM@s-GMSi).
[0029] The IM@s-GMSi obtained in this example has a diameter of 345±5nm and a hierarchical structure. Its primary most probable pore size is about 11nm, its secondary most probable pore size is about 30nm, and its specific surface area is 167.0m 2 / g; compared with particles with a single pore size, it can effectively avoid the blockage of the proton transmission path.
[0030] Example 3
[0031] Synthesis of aromatic ether polybenzimidazole (OPBI):
[0032] 8.834g (0.02mol) of 3,3'-diaminobenzidine (DAB) and 6.840g (0.024mol) of 4,4'-dimethyl ether dicarboxylic acid (OBA) were mixed, and then 30ml of PPMA solvent (a mixed solvent of phosphorus pentoxide and methane sulfonic acid, wherein the mass ratio of phosphorus pentoxide to methane sulfonic acid was 1:10) was added, and the mixture was reacted at 140°C for 2h under mechanical stirring and nitrogen protection. After reacting at 180°C for 7h, the mixture was poured into deionized water to obtain a black long strip polymer. After the polymer was crushed, it was first washed with deionized water for 5 times, and then added to a 10wt% sodium bicarbonate solution, washed at 40°C for 48h, washed with deionized water until the solution was neutral, filtered, and then vacuum dried at 100°C for 24h to obtain aromatic ether polybenzimidazole (OPBI).
[0033] Example 4
[0034] 1) IM@s-GMSi obtained in Example 2 and OPBI obtained in Example 3 were added to N,N-dimethylformamide solution, respectively, the concentration of IM@s-GMSi and OPBI in N,N-dimethylformamide solution was 42 g / L, and then the two solutions were mixed into a casting solution, wherein the mass ratio of IM@s-GMSi to OPBI was 2:98, and ultrasonic dispersion was uniform. Pour on a clean glass plate, dry at 80°C for 14h, then dry at 110°C for 28h, and then vacuum dry at 120°C for 10h to obtain a hybrid membrane.
[0035] 2) The hybrid membrane obtained in step 1) is immersed in a phosphoric acid solution with a mass fraction of 70%, immersed at 80°C for 24 hours, and then the excess phosphoric acid on the surface of the hybrid membrane is wiped off with filter paper, and dried at 120°C for 3 hours to obtain a polybenzimidazole / porous SiO2 microsphere hybrid high-temperature membrane. The obtained hybrid high-temperature membrane has a temperature of 255°C when the thermal weight loss is 5%, and has excellent thermal stability. While maintaining good mechanical strength, its phosphoric acid doping level is 336.0%, and the proton conductivity at 160°C and 200°C is 61.4mS / cm and 84.9mS / cm, respectively.
[0036] Example 5
[0037] 1) IM@s-GMSi obtained in Example 2 and OPBI obtained in Example 3 were added to N, N-dimethylacetamide solution, respectively, the concentration of IM@s-GMSi and OPBI in N, N-dimethylacetamide solution was 46 g / L, and then the two solutions were mixed into a casting solution, wherein the mass ratio of IM@s-GMSi to OPBI was 5:95, and ultrasonic dispersion was uniform. Pour on a clean glass plate, dry at 90°C for 14h, then dry at 110°C for 16h, and then vacuum dry at 100°C for 18h to obtain a hybrid membrane.
[0038] 2) Soak the hybrid membrane obtained in step 1) in a 90% by mass phosphoric acid solution at 110°C for 24 hours, wipe off the excess phosphoric acid on the surface of the hybrid membrane with filter paper, and dry at 110°C for 4 hours to obtain a polybenzimidazole / porous SiO2 microsphere hybrid high-temperature membrane. The obtained hybrid high-temperature membrane has an excellent thermal stability at a temperature of 240°C when the thermal weight loss is 5%. While maintaining good mechanical strength, its phosphoric acid doping level is 354.2%, and the proton conductivity at 160°C and 200°C is 82.1mS / cm and 115.4mS / cm, respectively.
[0039] Example 6
[0040] 1) IM@s-GMSi obtained in Example 2 and OPBI obtained in Example 3 were added to N, N-dimethylacetamide solution, respectively, the concentration of IM@s-GMSi and OPBI in N, N-dimethylacetamide solution was 45 g / L, and then the two solutions were mixed into a casting solution, wherein the mass ratio of IM@s-GMSi to OPBI was 8:92, and ultrasonic dispersion was uniform. Pour on a clean glass plate, dry at 80°C for 24h, dry at 120°C for 24h, and then vacuum dry at 120°C for 12h to obtain a hybrid membrane.
[0041] 2) Soak the hybrid membrane obtained in step 1) in a phosphoric acid solution with a mass fraction of 85% at 120°C for 24 hours, wipe off the excess phosphoric acid on the surface of the hybrid membrane with filter paper, and dry at 120°C for 3 hours to obtain a polybenzimidazole / porous SiO2 microsphere hybrid high-temperature membrane. The obtained hybrid high-temperature membrane has a temperature of 256°C when the thermal weight loss is 5%, and has excellent thermal stability. While maintaining good mechanical strength, its phosphoric acid doping level is 362.0%, and the proton conductivity at 160°C and 200°C is 101.5mS / cm and 122.0mS / cm, respectively.
[0042] Example 7
[0043] 1) IM@s-GMSi obtained in Example 2 and OPBI obtained in Example 3 were added to a dimethyl sulfoxide solution, respectively, the concentration of IM@s-GMSi and OPBI in the dimethyl sulfoxide solution was 49 g / L, and the two solutions were mixed into a casting solution, wherein the mass ratio of IM@s-GMSi to OPBI was 10:90, and ultrasonic dispersion was uniform. Pour onto a clean glass plate, dry at 80°C for 24h, then dry at 105°C for 24h, and then vacuum dry at 120°C for 12h to obtain a hybrid membrane.
[0044] 2) Soak the hybrid membrane obtained in step 1) in a phosphoric acid solution with a mass fraction of 85% at 120°C for 24 hours, wipe off the excess phosphoric acid on the surface of the hybrid membrane with filter paper, and dry at 120°C for 3 hours to obtain a polybenzimidazole / porous SiO2 microsphere hybrid high-temperature membrane. The obtained hybrid high-temperature membrane has a temperature of 212°C when the thermal weight loss is 5%, and has excellent thermal stability. While maintaining good mechanical strength, its phosphoric acid doping level is 371.2%, and the proton conductivity at 160°C and 200°C is 108.7mS / cm and 145.1mS / cm, respectively.
[0045] Example 8
[0046] 1) IM@s-GMSi obtained in Example 2 and OPBI obtained in Example 3 were added to a dimethyl sulfoxide solution, respectively, the concentration of IM@s-GMSi and OPBI in the dimethyl sulfoxide solution was 48 g / L, and the two solutions were mixed into a casting solution, wherein the mass ratio of IM@s-GMSi to OPBI was 15:85, and ultrasonic dispersion was uniform. Poured onto a clean glass plate, dried at 85°C for 24h, then dried at 110°C for 15h, and then vacuum dried at 105°C for 11h, thereby obtaining a hybrid membrane.
[0047] 2) Soak the hybrid membrane obtained in step 1) in a 75% by mass phosphoric acid solution at 100°C for 24 hours, wipe off the excess phosphoric acid on the surface of the hybrid membrane with filter paper, and dry at 100°C for 4 hours to obtain a polybenzimidazole / porous SiO2 microsphere hybrid high-temperature membrane. The obtained hybrid high-temperature membrane has an excellent thermal stability at a temperature of 220°C when the thermal weight loss is 5%. While maintaining good mechanical strength, its phosphoric acid doping level is 445.6%, and the proton conductivity at 160°C and 200°C is 44.4mS / cm and 55.3mS / cm, respectively.
[0048] Comparative Example 1
[0049] Lin et al. (Journal: Applied Surface Science, Title: Protic ionic liquid / functionalized graphene oxide hybrid membranes for high temperature protonexchange membrane fuel cell applications) prepared a series of 1-(3-aminopropyl)-3-methylimidazolium bromide ([APMIm][Br]) functionalized graphene oxide ([APMIm][Br]-GO) and 1-methylimidazolium trifluoromethanesulfonate ([MIm][TfO]) as fillers and proton carriers for high temperature hybrid proton exchange membranes (PEMs), respectively. The incorporation of an appropriate amount of [APMIm][Br]-GO significantly improved the proton conductivity of the hybrid membrane, with the highest proton conductivity of 14.8 mS / cm at 160°C.
[0050] In summary, the polybenzimidazole / porous SiO2 microsphere hybrid high-temperature membrane obtained in Comparative Example 1 and the present invention differ in terms of matrix and filler type, raw material ratio, process and parameters. The performance of the samples prepared in Examples 4-8 are all higher than the various properties of the materials obtained in Comparative Example 1. Therefore, the materials obtained in the present invention have more excellent performance. Comparative curves of phosphate adsorption behavior of polybenzimidazole / porous SiO2 microsphere hybrid high-temperature membranes obtained from Examples 4-8 Figure 1It can be seen that the acid adsorption level of the hybrid membrane obtained by the present invention is constantly improving, and in the first 3 hours, the mass of phosphoric acid adsorbed by the hybrid membrane is close to 3 times its own mass, showing a fast phosphoric acid adsorption rate. This is attributed to the hierarchical pore structure of the SiO2 microspheres, which constructs more unobstructed proton conduction channels and a large specific surface area, providing more acid adsorption sites, and the imidazole filled in the pores provides more proton hopping sites, which helps to improve the proton conductivity of the hybrid membrane. Figure 2 It can be seen that when the added mass proportion of porous SiO2 microspheres is less than 10%, the proton conductivity of the hybrid membrane increases with the increase of the doping content of the porous SiO2 microspheres, but when the mass proportion of the porous SiO2 microspheres is greater than 10%, the proton conductivity of the hybrid membrane decreases significantly with the increase of the added mass proportion of the porous SiO2 microspheres. It can be concluded that the greater the amount of porous SiO2 microspheres added, the greater the proton conductivity of the hybrid membrane. In addition, the hybrid membrane obtained in step 1) of Example 7 of the present invention was characterized in morphology (see Figure 3 and Figure 4 ),from Figure 3 The surface scanning electron microscopy image shows that the porous SiO2 microspheres are evenly distributed in the membrane. Figure 4 The cross-sectional SEM image shows that wrinkles appear on the membrane cross-section, which is the result of hydrogen bonding between the porous SiO2 microspheres and the polymer matrix. Figure 4 In the enlarged image, it can be seen that the porous SiO2 microspheres and polybenzimidazole spontaneously form a specific network state through hydrogen bond interactions without external intervention, and this network state presents different structural distributions in different directions in space. The diameter of the porous SiO2 microspheres (IM@s-GMSi) obtained by the present invention is at the nm level and has a hierarchical structure. Its primary most probable pore size is ≤15nm and its secondary most probable pore size is ≤35nm. It has a hierarchical porous structure, which can effectively avoid blockage of the proton transmission path compared to particles with a single pore size. This structure gives the hybrid membrane excellent acid absorption capacity. The tensile curve of the phosphoric acid-doped hybrid membrane obtained in Example 7 Figure 5It can be seen that when the doping content of IM@s-GMSi microspheres is 10%, the tensile strength of the polybenzimidazole / porous SiO2 microsphere hybrid high-temperature membrane is 8MPa, which meets the performance requirements of high-temperature proton exchange membrane fuel cells. The raw material component ratios and process parameters used in Examples 4-8 of the present invention are different, and the final material properties are different. The temperature when the thermal weight loss is 5% is greater than 210°C, that is, it has high-temperature thermal stability, and at the same time still has high electrical conductivity and mechanical properties under high temperature conditions. In summary, it can be concluded that the ultimate excellent performance of the material obtained by the present invention is not determined by a single process or parameter, but is achieved by the coordinated regulation of raw materials, ratios, processes and process parameters, and only within the scope of protection of the claims of the present invention can the best comprehensive performance of the material obtained by the present invention be achieved.
Claims
1. Polybenzimidazole / porous SiO2 microsphere hybrid high temperature membrane, characterized in that: The hybrid high-temperature membrane is mainly composed of soluble aromatic ether polybenzimidazole (hereinafter referred to as aromatic ether polybenzimidazole), sulfonic acid group and imidazole group modified hierarchical porous SiO2 microspheres (hereinafter referred to as porous SiO2 microspheres); the structure and chemical formula of the porous SiO2 microspheres are shown in Figure 6.
2. The polybenzimidazole / porous SiO2 microsphere hybrid high temperature membrane according to claim 1, characterized in that: The hybrid high temperature membrane, its preparation method comprises the following steps: The porous SiO2 microspheres and the aromatic ether type polybenzimidazole are dispersed in a solvent in a mass ratio of 1:99 to 1:4 to form dispersion 1 and dispersion 2, respectively. The concentrations of the porous SiO2 microspheres and the aromatic ether type polybenzimidazole in the solvent are both 40 to 50 g / L. The dispersion 1 and the dispersion 2 are mixed into a casting solution, ultrasonically dispersed evenly, poured onto a clean glass plate, dried at 80 to 120°C for 30 to 50 h, and then vacuum dried at 100 to 120°C for 10 to 2 After 10 hours, a hybrid membrane is obtained, and then the hybrid membrane is immersed in a phosphoric acid solution with a mass fraction of 70-90%, and immersed at 80-130°C for 24-48 hours, and then the excess phosphoric acid on the surface of the hybrid membrane is wiped off with filter paper, and then dried at 100-120°C for 3-5 hours to obtain a polybenzimidazole / porous SiO2 microsphere hybrid high-temperature membrane; the solvent is one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone or dimethyl sulfoxide.
3. The polybenzimidazole / porous SiO2 microsphere hybrid high temperature membrane according to claim 1, characterized in that: The preparation method of the porous SiO2 microspheres comprises the following steps: (1) Hexadecyltrimethylammonium bromide (CTAB) and urea are mixed in a mass ratio of 4:3 to 5:2, and deionized water is added and stirred until dissolved, wherein the total mass concentration of the CATB and urea in the deionized water is 30 to 50 g / L, and then cyclohexane, isopropanol and tetraethyl orthosilicate (TEOS) solution are added under stirring, wherein the volume ratios of cyclohexane, isopropanol and tetraethyl orthosilicate (TEOS) to deionized water are 60 to 90 vol. %: 1, 2 to 5 vol. % respectively. :1 and 5-10vol.%:1, continue stirring at 30-50°C for 20-60min, continue stirring at 70-90°C for 12-24h, then cool down, add anhydrous ethanol solution of the same volume as deionized water, centrifuge at 8000-10000r / min for 5-10min, wash with ethanol and deionized water for 3-5 times, dry under vacuum at 60-80°C for 20-30h, and calcine at 500-600°C for 4-8h to obtain hierarchical porous SiO2 microspheres; (2) dissolving the hierarchical porous SiO2 microspheres obtained in step (1) in toluene, wherein the concentration of the hierarchical porous SiO2 microspheres is 10-20 g / L, adding triethylamine, wherein the volume ratio of triethylamine to toluene is 1:400-1:300, stirring and ultrasonicating for 30-60 min, and then adding (3-mercaptopropyl)trimethoxysilane (MPTS) under magnetic stirring, wherein the molar ratio of MPTS to the hierarchical porous SiO2 microspheres is 1:5-3:5, reacting at room temperature for 5-12 h, centrifuging, washing with ethanol 3-5 times, drying at 60-80° C. for 4-10 h, and then dispersing in 30%-40% hydrogen peroxide, stirring at room temperature for 3-8 h, washing with ethanol and deionized water 3-5 times respectively, and drying at 60-80° C. for 6-12 h to obtain sulfonated hierarchical porous SiO2 microspheres; (3) Degassing the sulfonated graded porous SiO2 microspheres obtained in step (2) at 90-120°C in vacuum, adding imidazole, wherein the mass ratio of the sulfonated SiO2 microspheres to imidazole is 1:20-1:10, and then evaporating and adsorbing at 90-120°C in vacuum for 5-30 hours to obtain porous SiO2 microspheres.
4. The polybenzimidazole / porous SiO2 microsphere hybrid high temperature membrane according to claim 1, characterized in that: The preparation method of the aromatic ether polybenzimidazole comprises the following steps: 3,3'-diaminobenzidine (DAB) and 4,4'-diphenyl ether dicarboxylic acid (OBA) are mixed in a molar ratio of 1:1 to 6:5, and then a PPMA solvent is added, wherein the concentrations of DAB and OBA in the PPMA solvent are both 1 to 2 mol / L, and the mixture is reacted at 140 to 190° C. for 8 to 10 hours under mechanical stirring and nitrogen protection, and poured into deionized water to obtain a black long strip polymer, and the polymer is crushed, and then washed with deionized water for 3 to 6 times, and then added to a 5 to 15 wt% sodium bicarbonate solution, and washed at 40 to 60° C. for 36 to 60 hours, and then washed with deionized water until the solution is neutral, filtered, and vacuum dried at 80 to 120° C. for 20 to 30 hours to obtain an aromatic ether type polybenzimidazole; the PPMA solvent is a mixture of phosphorus pentoxide and methane sulfonic acid, and the mass ratio of the phosphorus pentoxide to methane sulfonic acid is 1:10 to 1:8; The synthetic route of the aromatic ether type polybenzimidazole is as follows: Wherein n is a positive integer, n=100~160.
5. Application of the polybenzimidazole / porous SiO2 microsphere hybrid high temperature membrane according to any of claims 1 to 4 in the field of high temperature proton exchange membrane fuel cells.
Citation Information
Cited By
Hollow mesoporous silica microspheres, and preparation method and application thereof
CN121672543A
Hierarchical-pore titanium dioxide super-particles as well as preparation method and application thereof
CN122324852A
